The Development of Research Skills in Nursing Postgraduate Training - Ferreira, Rogério (2022)
Abstract: The objective of this study was to understand the contribution of postgraduate training to the development of research skills, aiming at their application in clinical practice. Method: This was a qualitative, exploratory, and descriptive study conducted with eight nurses in the Local Health Unit of Baixo Alentejo, in Portugal, who had postgraduate training. The researchers conducted a group interview, or discussion group, using a semi-structured interview, which was assessed by two reviewers. The data were submitted to content analysis, and the results underwent a validation process with the participants and two reviewers. This study was approved by the institution’s ethics committee. Result: In terms of the research skills developed in nursing postgraduate education, the following indicators emerged from the participants’ discourse: understanding the research process, searching databases, developing literature reviews, assessing the quality of articles, developing research projects, communicating about science, and translating knowledge into clinical practice. Conclusion: The participants developed research skills in their nursing postgraduate training and reported developing these skills in their clinical practice.